Prominence of Improved Cook Stove (ICS) in Rural Area: End-Users Perspective - Khadka, Gopal (Nepalese Journal of Development and Rural Studies, 2020)
Improved cook stove (ICS) indicates improved form of traditional cook stove. It is more effective, efficient and safer to use. ICS is popular in rural villages of Nepal as a new innovation of clean cooking mechanism. To explore the end users views about the prominence of ICS in rural settings of urban areas, this study is conducted as the title of prominence of improved cook stove in rural areas: end-users perspectives. It is based on the theoretical assumption of cultural feminism. It employs exploratory research design and is based on both primary and secondary sources of data. The study revealed that there is high prominence of ICS in rural farm based society in Nepal. Women are end-users of ICS. Through women perspectives, health and sanitation; easy operation; time and resource saver; low maintenance are its major prominence. ICS helps to reduce the untiring busy schedule of women in household activities. It suggests that concerned authorities should make effective institutional frameworks to empower women in their homeland by optimum utilization of leisure time made possible by the use of ICS.